Towards Low-Emission Coastal Tourism: Integrating Life Cycle Assessment And Nature-Based Solutions At Indrayanti Beach, Indonesia (Architecture Image Studies, 2026)
The growth of coastal tourism in tropical regions has accelerated environmental pressures, particularly through elevated carbon emissions and ecosystem degradation. This study proposes an integrated framework for low-emission tourism development at Indrayanti Beach, Indonesia, by combining Life Cycle Assessment (LCA) with Coastal Ecosystem Services (CES). Key interventions—including centralized wastewater treatment with solar-biogas energy, greywater recycling, sludge composting, and electric mobility infrastructure—are analyzed for their carbon reduction potential and feasibility. Results demonstrate that integrated WWTP systems can lower emissions by up to 30%, while electrified transportation can reduce sectoral emissions by 70%. By embedding CES principles, the framework strengthens ecological resilience and community participation. Policy recommendations highlight the role of adaptive carbon standards, fiscal incentives, and digital monitoring in achieving the 2060 net-zero goal. This study presents a transferable model for climate-compatible tourism planning in vulnerable coastal regions.